Meaningful Learning Practices in Islamic Education: A Qualitative Exploration of Planning, Implementation, and Evaluation - Muhammad Maulana Malik Ibrohim; Udin Supriadi; Agus Fakhruddin (Didaktika: Jurnal Kependidikan, 2025)
This research explores the implementation of meaningful learning in Islamic Religious Education (PAI) classes at two Islamic-based senior high schools in Bandung: SMA OMNI Bintang Madani and SMA Mutiara Bunda. Using a qualitative descriptive approach, the study examines planning, implementation, and evaluation stages of meaningful learning as applied in both schools. The findings reveal that both institutions apply contextual, student-centered, and value-based learning strategies, supported by continuous teacher training, integrated curriculum design, and holistic assessments. SMA OMNI adopts a structured PDCA model, while SMA Mutiara Bunda emphasizes flexibility and student agency. The results suggest that meaningful learning not only strengthens religious understanding but also enhances students’ reflective thinking, creativity, and character development. This study provides a practical model for integrating Ausubel’s theory with 21st-century skills and Islamic education values.